Edited GluR2, a gatekeeper for motor neurone survival? - Buckingham, S; Kwak, S; Jones, A; Blackshaw, SE; Sattelle, D (2008)
Amyotrophic lateral sclerosis (ALS) is a progressive degenerative disorder of motor neurones. Although the genetic basis of familial forms of ALS has been well explored, the molecular basis of sporadic ALS is less well understood. Recent evidence has linked sporadic ALS with the failure to edit key residues in ionotropic glutamate receptors, resulting in excessive influx of calcium ions into motor neurones which in turn triggers cell death. Here we suggest that edited AMPA glutamate (GluR2) receptor subunits serve as gatekeepers for motor neurone survival.